A biomimetic approach to modulating the sustained release of fibroblast growth factor 2 from fibrin microthread scaffolds - Meagan E. Carnes; Cailin R. Gonyea; Jeannine M. Coburn; George D. Pins (Exploration of BioMat-X, 2024)
Aim: The pleiotropic effect of fibroblast growth factor 2 (FGF2) on promoting myogenesis, angiogenesis, and innervation makes it an ideal growth factor for treating volumetric muscle loss (VML) injuries. While an initial delivery of FGF2 has demonstrated enhanced regenerative potential, the sustained delivery of FGF2 from scaffolds with robust structural properties as well as biophysical and biochemical signaling cues has yet to be explored for treating VML. The goal of this study is to develop an instructive fibrin microthread scaffold with intrinsic topographic alignment cues as well as regenerative signaling cues and a physiologically relevant, sustained release of FGF2 to direct myogenesis and ultimately enhance functional muscle regeneration. Methods: Heparin was passively adsorbed or carbodiimide-conjugated to microthreads, creating a biomimetic binding strategy, mimicking FGF2 sequestration in the extracellular matrix (ECM). It was also evaluated whether FGF2 incorporated into fibrin microthreads would yield sustained release. It was hypothesized that heparin-conjugated and co-incorporated (co-inc) fibrin microthreads would facilitate sustained release of FGF2 from the scaffold and enhance in vitro myoblast proliferation and outgrowth. Results: Toluidine blue staining and Fourier transform infrared spectroscopy confirmed that carbodiimide-conjugated heparin bound to fibrin microthreads in a dose-dependent manner. Release kinetics revealed that heparin-conjugated fibrin microthreads exhibited sustained release of FGF2 over a period of one week. An in vitro assay demonstrated that FGF2 released from microthreads remained bioactive, stimulating myoblast proliferation over four days. Finally, a cellular outgrowth assay suggests that FGF2 promotes increased outgrowth onto microthreads. Conclusions: It was anticipated that the combined effects of fibrin microthread structural properties, topographic alignment cues, and FGF2 release profiles will facilitate the fabrication of a biomimetic scaffold that enhances the regeneration of functional muscle tissue for the treatment of VML injuries.